Virtual Laboratories Development Using 3D Environments - Oliveira, Toni Amorim; Marranghello, Norian [UNESP]; Rodrigues Silva, Alexandre Cesar [UNESP]; Pereira, Aledir Silveira [UNESP]; Neto, FMM; DeSouza, R; Gomes, AS (Igi Global, 2016)
3D virtual worlds or metaverses are immersion environments that allow the simulation of some real environment characteristics such as sound and gravity. In this chapter we describe the development of a 3D virtual environment as well as its integration with Moodle platform using Sloodle plugin. We discuss related works dedicated to the development of virtual laboratories. We also describe the main software used and how to perform the settings required for the operation of the environment. To introduce the developed software utilization we present a laboratory built for teaching subjects based on multiple intelligences theory defined by Gardner.